(3QSGdI aj Yde GdMQhas ((3eMeO HgGA GdOjf dLGjQi GdMSjfi s)
(3ChdgG (B:s
(3jGeOYi HGdTWGQI GgJOi hGSeY Edi Yde GdMQha GQLY GdGSe s
(3BNQgG (B:s
(3CfJ GdMb djS GdgGOi EdGgh JeJ HGdNjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B89) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs